Daños de Tyrophagus putrescentiae (Schrank) (Acari: Acaridae) en explotaciones de champiñon de Castill-La Mancha - Navarro, M.J.=700 1 Escudero, A.; Gea, F.J.; Ferragut, F.
(Es, En)
ilus., 14 ref.
Keywords: TYROFHAGUS; ACARINA; AGARICUS BISPORUS; DAÑOS; DIAGNOSTICO; ESPAÑA